Tronquée Solutions of the Third and Fourth Painlevé Equations - Xia, X. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
Recently, in a paper by Lin, Dai, and Tibboel, it was shown that the third and fourth Painlevé equations have tronquée and tritronquée solutions. We obtain global information about these tronquée and tritronquée solutions. We find their sectors of analyticity, their Borel summed representations in these sectors, as well as the asymptotic position of the singularities near the boundaries of the analyticity sectors. We also correct slight errors in the paper mentioned.